The Influence of Human Resource Development, Work Culture, And Motivation on Employee Performance of The Secretariat General of DPR RI Through Job Satisfaction - Andrie Widianto; Parwoto Parwoto (International Journal Labs, 2025)
This study aims to examine the effect of human resource development (HRD), work culture, and motivation on employee performance at the Secretariat General (Setjen) of the DPR RI, with job satisfaction as an intervening variable. The methodology used in this research is quantitative, involving 95 respondents consisting of all State Civil Apparatus (ASN) functional officials under the guidance of the Secretariat General of the DPR RI in 2022. This research applies a saturated sample technique, where the entire population is used as a sample. For data analysis, the Structural Equation Modeling (SEM) method was used. The results showed that HR development had no effect on employee performance, and no effect on job satisfaction. On the other hand, work culture also has no direct effect on performance, but has a positive and significant effect on job satisfaction. Motivation is proven to have a positive and significant impact on employee performance, although it has no effect on job satisfaction. In addition, job satisfaction is shown to have a positive and significant influence on performance. An important finding of this study is that HR development does not affect employee performance, even with job satisfaction as a mediator. In contrast, work culture shows a positive and significant influence on employee performance when job satisfaction is used as a mediator, while motivation does not show the same effect. This study is the first of its kind conducted at the Secretariat General of the House of Representatives and the results may serve as an impetus for researchers to provide further analysis to improve employee performance.